Effect of Macronutrient Combination on Survivorship, Growth, and Nutritional Content of Black Soldier Fly Larvae (Hermetia illucens) - Sari, Anggraeni Arum; Kinasih, Ida; Sari, Dian Anggria; Putra, Ramadhani Eka (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2021)
Larvae of black soldier fly (Hermetia illucens) has been widely applied as a biological agent for biodegradable wastes upcycling through bioconversion process. However, most of the biodegradable wastes produced from economic activities other than industrial is heterogenous. This may cause some physiological change which may alter the survivorship, growth, and efficiency of the bioconversion process. In this study, the substrate combination of macronutrients provided to black soldier fly larvae were observed to understand the larvae ability to degrade organic waste from economic activities. The substrat proportion consist of three major macronutrients (carbohydrate, protein, and lipid) and made of a mixture of decayed cabbage (Brassica oleracea) (source of carbohydrate), shark catfish (Pangasius sp.) (source of protein), and avocado (Persea americana) (source of lipid) which consisted of four types of substrate namely high fiber, high protein, high lipid, and balance. The feeding rate was 100 mg/larvae/day which provides every three days until 50% of larvae metamorphosed into prepupae. Mortality rate, the weight of larvae, and weight of residue (undigested substrate) were measured during substrate replacement and used to calculated survivorship rate, ECD (Efficiency of Conversion Digested-feed), AD (Approximate digestibility), and WRI (Waste Reduction Index). The proximate analysis also conducted on the harvested larvae biomass. The larvae group fed on high protein substrate showed best survivorship (64,75±2,60%), growth rate (2,97±0,166 mg/larvae/day), and AD (57,39±3,39) while the highest WRI recorded for larvae group fed on high fiber substrate and the highest ECD recorded for larvae group fed on high lipid substrate. The proximate analysis showed the best nutritional content of prepupae of larvae group fed on high protein substrate. It can be concluded that the proportion of macronutrients of substrate effect the growth and bioconversion performance of black soldier fly larvae. Some strategies related to the optimization of the bioconversion process for heterogeny substrate are discussed.Keywords: biodegradable wastes, black soldier fly, heterogeneity, growth, nutritional content, survivorship.